The CSF concentration of ADMA, but not of ET-1, is correlated with the occurrence and severity of cerebral vasospasm after subarachnoid hemorrhage - Jung, Carla Sabine (Neuroscience letters, 2012)
Under physiological conditions, vasoconstrictors and vasodilators are counterbalanced. After aneurysmal subarachnoid hemorrhage (SAH) disturbance of this equilibrium may evoke delayed cerebral vasospasm (CVS) leading to delayed cerebral ischemia (DCI). Most studies examined either the vasoconstrictor endothelin-1 (ET-1) or the vasodilative pathway of nitric oxide (NO) and did not include investigations regarding the relationship between vasospasm and ischemia. Asymmetric dimethyl-l-arginine (ADMA), an endogenous inhibitor of nitric oxide synthase (NOS), decreases the concentration of NO. Studies have correlated increasing concentrations of ADMA with the course and degree of CVS after SAH. We sought to determine, if ADMA and endothelin-1 (ET-1) are associated with CVS and/or DCI after SAH. CSF concentrations of ADMA and ET-1 were retrospectively determined in 30 patients after SAH and in controls. CVS was detected clinically and by arteriogaphy. DCI was monitored by follow-up CT scans. 17 patients developed arteriographic CVS and 4 patients developed DCI. ADMA but not ET-1 concentrations were correlated with occurrence and degree of CVS. However, ET-1 concentrations were correlated with WFNS grade on admission. Neither ADMA nor ET-1 correlated with DCI in this cohort. ET-1 concentrations seem to be associated with the impact of the SAH bleed. ADMA may be directly involved in the development and resolution of CVS after SAH via inhibition of NOS disturbing the balance of vasodilative and -constrictive components.